Fitorremediação de clorobenzenos em lodo de esgoto com aeração e compostagem - Fernanda Vieira de Oliveira (2020)
Bioremediation and composting are important techniques for the stabilization processes of sewage sludge, making it safer for agricultural use. However, in the composting process, to mix carbonaceous material with sewage sludge is necessary but this material is not always easily available. Thus, the cultivation of plants directly in the sewage sludge can promote phytoremediation of toxic organic substances and also provide carbonaceous material for the composting of this waste. Thus, the present study aimed to evaluate the content of some chlorobenzene congeners in composted sewage sludge, after the cultivation of Pennisetum purpureum with different aeration periods. The experiment was conducted in a randomized block design with treatments distributed in a 2 x 5 factorial scheme, with four replicates, corresponding to the presence or absence of Pennisetum purpureum cultivation in sewage sludge with planting density of 50 plants per m2, from the planting of cuttings, combined with five periods of intermittent aeration for 30 minutes: 0; 14; 28; 42 and 60 days, with an air flow of 1,059 dm3 h-1 kg-1 of volatile solids. After 60 days of cultivation, the grass was cut, crushed and incorporated into the sewage sludge and the mixture composted for 60 days. At the end of the cultivation and composting, analyses of the concentrations of 1,4-DCB and 1,3,5-TCB of the organic material were made. The levels of 1,4-DCB and 1,3,5-TCB in sewage sludge were lower in the absence of plant cultivation in this residue. Aerations of sewage sludge for a period of 60 days, for 1,4-DCB, and 45 days, for 1,3,5-TCB, also promoted the greatest reductions of these substances in sewage sludge. The composting of sewage sludge after the aeration and cultivation period did not change the levels of 1,3,5-TCB, however, it significantly reduced the levels of 1,4-DCB in this residue.